IT GOVERNANCE IN THE BANKING SECTOR: EVIDENCE FROM ITALY, GERMANY, FRANCE AND SPAIN - Ida Claudia Panetta; Sabrina Leo; Fabrizio Santoboni; Gianfranco Vento (Economic Review)
The paper analyzes Information Technology (IT) governance disclosure on a sample of the major 20 EU banks (from Italy, Germany, France and Spain) to observe if, how and where banks report on their IT governance issues. Since IT governance (like other aspects of banking business) can be influenced by regulatory environment, we examine whether any differences in supervisor attitude to IT concern will induce differences in IT governance across countries. IT is an intrinsic component of banks’ operational functioning; it is a key resource in developing and supporting banking services, enabling institutions’ strategies, and it is essential for almost all banking processes and distribution channels. IT and data architectures are also becoming even more necessary to improve banks’ risk management process, and support the broad management of financial risks. Due to this increasing relevance of IT, it is necessary to pay more attention to IT governance as an integral part of banking corporate governance, making sure that IT processes are fully integrated into the life cycle of business process and used as an enhancer of organizational strategy and goals. Recurring to IT governance transparency, as a key mechanism of corporate governance, we: i) elaborate an original IT governance framework; ii) perform a content analysis on banks public disclosure and a selected number of supervisors’ official documents (2008-2015) to build up IT governance indices; iii) run a multidimensional analysis to detect causal relationships between variables. Our analysis indicates that differences in the level of IT governance disclosure are bank specific and not related to country’s institutional settings; we also observed an increasing consistent attention  of both supervisors and banks to IT issues starting from 2013.